Strategi Pengembangan Karier PNS Fungsional Umum di Institut Pertanian Bogor - Gandi Aria Wijaya; M. Syamsul Ma'arif; Anggraini Sukmawati (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
The main issues in the field of human resources is a state civil officials on the quality and distribution of civil servants, therefore we need a research to know the civil servant career development strategy. Process and career development should be professional career development oriented of civil servants which means not only the structural purpose, but also to developing expertise towards functional. Thus, the position of the functional has a role as equal partners in a structural position. The purpose of this study is to identify what are the main priorities of the factors, actors and objectives as well as the recommendation of alternative strategies are most influential on the development of common functional civil servants career in IPB. The research was conducted at IPB and the Bureau of Personnel Culture and Education Ministry Secretariat using descriptive analysis and AHP (Analytical Hierarchy Process) methods. The results of the descriptive analysis is from 1.500 civil servants education personnel only 14,3% certain functional officials in IPB, thus 83,7% is common functional PNS included structural officials which selectively will be converted to be specific functional civil service officials. Results obtained from AHP processing the alternative strategy most recommended is the establishment of assessment centers (0,482) by actor Vice Rector of Resources and Strategic Studies (0,498), through the strengthening of organizational factors (0,357) with the aim of increasing professionalism (0,600), that all are the main priorities which influence to the development of a common functional IPB civil servants career.Keywords: civil servant quality and distribution, professionalism, carrier development strategy, assesment center